Acoustical design strategies for open-plan workstations in green office buildings / Nurul Amira Abd Jalil - Nurul Amira , Abd Jalil (2018)
Although it was well established that acoustic is a significant environmental stressor, it was often overlooked as an environmental element in office design. Being a quarter part of indoor environmental quality (IEQ), the introduction of green building movement was anticipated to bring improvement to all aspects of the IEQ including acoustics. Unfortunately, it did not seem to be the case. At present, office is the most prominent type of workplaces, and open-plan office is the most favourable type of offices. Acoustic quality in offices is essential as people spend most of their waking hours in the office. Good acoustic quality is achievable through design measures which consciously complement the acoustical environment. With regards to green office buildings in Malaysia, there is a gap in knowledge where this area of study has yet to be explored. Hence, before any proposal of acoustical design measures can be made, understanding of the underlying acoustic conditions in open-plan offices in green office buildings in Malaysia is essential. Therefore, the first two objectives of this study are to evaluate the level of acoustic quality in selected open-plan offices and identify the green design elements that influence the acoustic quality in those same open-plan offices. Understanding the basic acoustic and design conditions would assist in the investigation of suitable alternatives of design strategies and variables, and the formulation of design measures that need to be taken to achieve acoustically comfortable open-plan offices. This study was done using the combination of case study through site visits, observations, and field measurement; as well as computer modelling and acoustic simulation on experimental open-plan office layouts. Data findings revealed that internal design elements such as partitions between workstations and the layout arrangements play a significant role in achieving speech privacy in open-plan offices. However, design measures should not be limited to internal design strategies alone as attention towards other design factors such the room geometry and consideration of all relevant acoustic parameters could help in attaining acoustically comfortable open-plan offices.